The Relationship Between the Theme and the Characters in the Novel of the Woman at Point Zero by Nawal El Saadawi - Kamayana, I Gusti Nyoman Putra; Dewi, Ni Luh Desy Suari; Dewi, Putu Chrisma (Pusat riset dan Inovasi Nasional, 2025)
The novel